Rheumatoid arthritis – symptoms, diagnosis, treatment - Machaj, Dominik; Płaczek, Alicja; Cyboran, Katarzyna; Siedlak, Agnieszka; Białas, Filip (Journal of Education, Health and Sport, 2022)
Rheumatoid arthritis is a systemic autoimmune disease of connective tissue of unknown etiology. Specific for it is the involvement of symmetrically small and medium-sized joints, leading to degradation of their structure, stiffening and muscle contractures. It is also characterized by extra-articular and generalized symptoms, such as fatigue, low-grade fever and sweating. It can occur with or without elevated RF and / or ACPA antibodies, causes disability and contributes to premature death. Drugs for this disease can be categorized into disease-modifying drugs as well as glucocorticosteroids and non-steroidal anti-inflammatory drugs. The first-line drug is methotrexate. In case of ineffectiveness of the treatment, biological treatment can be started.